Risk factor profile of young adults with acute myocardial infarction: a preliminary finding - Mohd Razib, Mohd Zhafri; Mohd Shah, Azarisman Shah; Ab Rahman, Jamalludin; Abdullah, Aszrin; Mohd. Shah, Aida Nur Sharini; A.Talib, Norlelawati; Mohamed Bakrim, Norbaiyah; Draman, Samsul (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Acute myocardial infarction (AMI) is a major cause of death around the world. There are limited studies of risk factor profile in young adults with AMI. This study aimed to assess the risk factor profile of young adults with AMI at the emergency department of Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang. This is a preliminary result of young adults (age between 18 to 45 years old) who presented to the emergency department of HTAA.